Deep eutectic solvent mediated synthesis of β-carbolines and related natural products via Pictet–Spengler reaction and aerobic oxidation - Bhuvana Narasimman (Tetrahedron Green Chem, 2025)
An eco-friendly, one-pot synthesis of β-carboline derivatives using deep eutectic solvent is reported. This protocol utilizes commercially available aldehydes and tryptamine, involving Pictet–Spengler cyclization followed by aerobic oxidation. This environmentally friendly methodology offers access to various β-carboline alkaloids Nitramarine, Nitraridine, Eudistomin U, Norharmane, Harmane, and their analogues in a single step with 30–68% yields.